Associação entre lócus de controle de saúde e benefício mínimo válido para tratamento em pacientes com dor lombar não específica - Vinicius Cunha Oliveira (2008)
Although it has been advocated that the interpretation of results from randomized clinical trials and meta-analyses should consider what patients believe to be the minimal worthwhile effect associated with treatment, it is still not known whether the opinions of patients with Low Back Pain (LBP) are associated with psychosocial factors such as health locus of control. This cross-sectional study investigated the association between the psychosocial factor of health locus of control and what patients with non-specific LBP consider to be the sufficiently important difference associated with two evidence based interventions. Eighty six LBP patients participated in the study. Patients health locus of control was assessed with the multidimensional health locus of control questionnaire. The opinions of the minimal worthwhile effect, currently known as Sufficiently Important Difference (SID) were assessed with a visual analog scale. Patients rated the SID associated with evidence based treatments for LBP such as motor control exercises and spinal manipulative therapy. After results of univariate analysis, multiple linear regression models including factors of external health locus of control (for motor control exercises) and external and internal health locus of control (for spinal manipulative therapy) were built to test their association with SID after adjusting for the severity of symptoms. Patients external locus of control was associated with higher levels of SID for motor control exercises (=0.74; 95%CI:0.05 to 1.42; p=0.035) but not manual therapy (=0.41; 95%CI:-0.44 to 1.27; p=0.337). Patients internal locus of control was not associated with SID for manual therapy (=0.62; 95%CI:-0.50 to 1.76; p=0.274). Patients with LBP who agree more strongly with the notion that others are responsible for their condition have higher sufficiently important difference with active treatments such as motor control exercises.